2012
DOI: 10.1785/0120110139
|View full text |Cite
|
Sign up to set email alerts
|

Seismicity and Seismotectonics Study in Southwestern Albania Using a Local Dense Seismic Network

Abstract: The Albanides represent a complex orogen made up of a heterogeneous tectonic nappe pile of Paleozoic, Mesozoic, and Cenozoic domains. Albania is tectonically active, and moderate to strong earthquakes have occurred in the past. However, abundant microseismicity has not been monitored and studied by a dense seismic network. During this study, a seismic network of 40 stations was deployed in southern Albania for one year. A total of 2113 microearthquakes were well located. The most accurately located events and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Serpetsidaki et al . [] repeated the same analysis in SW Albania, using again a temporary seismic network of 40 stations but a much larger data set (~810 solutions). This time the stress inversion results in all six subareas are in general consistent with ours, both for σ 1 axes (azimuths from N62°E to N233°E, plunges 3°–30°) and σ 3 axes (azimuths from N91°E to N318°E).…”
Section: Description Of Stress Inversion Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Serpetsidaki et al . [] repeated the same analysis in SW Albania, using again a temporary seismic network of 40 stations but a much larger data set (~810 solutions). This time the stress inversion results in all six subareas are in general consistent with ours, both for σ 1 axes (azimuths from N62°E to N233°E, plunges 3°–30°) and σ 3 axes (azimuths from N91°E to N318°E).…”
Section: Description Of Stress Inversion Resultsmentioning
confidence: 99%
“…Based on analysis of gravity observations, Shaw and Jackson [2010] suggested that the elastic part of the Ionian Sea lithosphere is flexed owing to the SW motion along KTF, which may explain the presence of a thrust component. Along Epirus and southern Albania low-angle thrust faulting dominates as a result of the continent-continent collision [Hatzfeld et al, 1995;Tselentis et al, 2006;Serpetsidaki et al, 2012]. To the south of Zakynthos lowangle thrust faulting occurs at the shallow dipping interface of the subduction.…”
Section: Western Greece and Southwestern Albaniamentioning
confidence: 99%
See 2 more Smart Citations
“…north-northeast (AG01, AG02, AG03, AG14, and AG15 sites), the GPS stations on the Albanian shoreline (GNSS stations KRYE, APOL, and RRAD) point toward the north-northwest ( Figure 2). The strain velocities in the internal region of southern Albania (GNSS stations LABO, DERV, and LESK) are perfectly parallel to the west-southwest direction of convergence, as documented by the slip vectors on the principal thrusts (Muço, 1994;Louvari et al, 2001;Serpetsidaki et al, 2012). This remarkable difference in the direction from the coastal to the internal sector is likely because of a strong mechanical coupling characterizing the Karaburuni-Sezani detachment (ALCS201) and the Durresi Offshore thrust (ALCS315).…”
Section: Discussionmentioning
confidence: 89%